The Effect of Service Quality on Customer Loyalty Mediated by Brand Image at Shopee Food in Bandung - Fiola Valentina Fasa; Akhmad Yunani (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this study was to evaluate and analyze the effect of service quality on Shopee Food customer loyalty in Bandung, to determine and analyze the effect of service quality on Shopee Food brand image in Bandung, to determine and analyze the effect of service quality on Shopee Food brand image in Bandung, to determine and analyze the role of brand image in mediating the effect of service quality on Shopee Food customer loyalty in Bandung. The research method used in this research is descriptive quantitative. The results showed that service quality did not have a significant impact on customer loyalty, this shows that improving service quality is not a top priority in an effort to strengthen customer loyalty. Service quality has a positive and significant effect on brand image. This shows that improving service quality will have a direct impact on the company's brand image. Brand image has a positive and significant effect on customer loyalty. This shows that the perception or image that customers have of the brand has a strong impact on how loyal they are to the brand. Service quality has a positive and significant effect on customer loyalty mediated by brand image. This means that brand image plays an important role in connecting service quality with customer loyalty.